Turbulent Film Condensation of Pure Vapors Flowing Normal to a Horizontal Condenser Tube - Constant Heat Flux at the Tube Wall - Sharma, Korada Viswanatha; B., Vijaya Lakshmi; T., Subrahmanyam; V., Dharma Rao (Universiti Malaysia Pahang, 2011)

(untitled)
A mathematical model is developed for the study of external turbulent film condensation of pure vapors flowing downward and normal to the axis of the condenser tube with constant heat flux condition maintained at the tube wall. The magnitude of interfacial shear is estimated for a given external flow condition of the vapor with the help of Colburn’s analogy. The average condensation heat transfer coefficients for different system conditions are evaluated. The present theory is compared with the available experimental and theoretical data in the literature and is found to be satisfactory.